The effect of non-punitive peer comparison and performance feedback on drivers' behavior using the telematics: The first randomized trial in Iran. (September 2022) - Ghamari, Azin; Rezaei, Nazila; Malekpour, Mohammad-Reza; Azadnajafabad, Sina; Jafari, Ayyoob; Ahmadi, Naser; Bhalla, Kavi; Shahraz, Saeid; Bose, Dipan; Farzadfar, Farshad
Abstract: Background: Aggressive driving is the leading behavior resulting in fatal or nonfatal disabling injuries. Therefore, programs with the main focus on driving behavior could reduce the risk of traffic injuries remarkably. We aimed to investigate the role of non-punitive performance feedback on drivers' behavior and evaluate the persistence of the altered behavior by using in-vehicle telematics. Methods: This study was done as a randomized controlled trial by repeated-measures design to evaluate the non-punitive behavioral intervention's efficacy on the behavioral transition to safer driving for 1, 289 bus and 104 taxi drivers. All participants were studied during 17 weeks through three stages: stage 0 (five weeks for collecting the baseline characteristics of the participants), stage 1 (nine weeks for randomizing the participants into intervention group or control group and sending the intervention group feedback via short message service), and stage 2 (three weeks for following-up the participants without sending feedback). The intervention group drivers received weekly text messages about the driving score and drivers' rank within their peer group.The study's primary outcome was the driver score changing pattern throughout the study calculated by a neuro-fuzzy scoring system composed of four factors: speed violation, harsh acceleration, harsh braking, and harsh turning. Results: Among the bus drivers, a significant positive effect of the intervention was found in stage 1 (P<0.0001) and in stage 2 (P<0.0001) regarding the calculated scoring system. Among the taxi drivers, a significant positive effect of the intervention was found in stage 1 (P<0.0001), but the effect was not significant in stage 2 (P=0.15). Conclusion: The results of this study were in favor of using telematics and its positive effect on driving performance. The reformed behavior persisted even after the intervention ceased. Practical Application: Behavioral interventions could be considered a promising strategy to enhance and promote safe driving performance.